Voicing Palestinian resistance through literary work: Analysis of metaphor in manshūrāt fidā’iyyah 'alā judrān isrāīl by Nizar Qabbani - Zulfa Khuriyatul Farah; Mustabir Halim; Ahmed Shbair; Amal Syahidin (Diwan: Jurnal Bahasa dan Sastra Arab, 2025)
Manshūrāt Fidā'iyyah 'alā Judrān Isrāīl is one of the iconic Palestinian resistance literature pieces composed by Nizar Qabbani. Although several scholars have analysed the poem, none have focused on the meaning and value of resistance. For this reason, this study aims to identify metaphors to emphasise the spirit of resistance in the poem. The descriptive qualitative method is used to achieve this goal. Data collected through documentation, reading, and note-taking techniques were then analysed through the stages of reduction, presentation, and conclusion drawing. The research findings show the types of metaphors consisting of objective (36.5%), human (22.2%), metaphysical (17.4%), actual (8.7%), living (6.3%), animate (4.7%), and inertia (3.9%). The metaphorical expression employed in the poetry carries profound and impactful meanings, serving as a powerful call for resistance against the occupiers. Through his verses, Qabbani underscores the enduring presence of Palestine and its people, asserting that no matter the efforts of Israel and its allies to obliterate them, Palestine will persevere and remain steadfast. Therefore, the metaphors in this poem are not just symbols, but are expected to form a cognitive awareness. On the other hand, Qabbani uses metaphors that are close to the perception of the Palestinian people to encourage resistance. Theoretically, this research has implications for strengthening semantic theory, especially human perception space, which has proven effective in revealing poetry's more profound and comprehensive meanings. While practically, this research has implications for amplifying the voicing of resistance through poetry and literary studies to defend humanity in Palestine.